1955
DOI: 10.1042/bj0610611
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of pentachloronitrobenzene and 2:3:4:6-tetrachloronitrobenzene and the formation of mercapturic acids in the rabbit

Abstract: In the rabbit 2:3:5:6-tetrachloronitrobenzene is metabolized by reduction of the nitro group, hydroxylation and mercapturic acid formation (Bray, Hybs, James & Thorpe, 1953). The last reaction is of particular interest since it is accompanied by loss of a nitro group directly attached to the benzene ring. Two further examples of this type of reaction were encountered when pentachloronitrobenzene and 2:3:4:6-tetrachloronitrobenzene were given to rabbits (Betts, James & Thorpe, 1953). A more detailed study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

1965
1965
2003
2003

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 9 publications
3
38
0
Order By: Relevance
“…The bulk of the substrate was found in the urine, only small amounts were excreted with the faeces. After Betts et al (1955) confirmed the results of Deichmann et al as PCP in the urine of rabbits was not excreted in a conjugated form, PCP seemed to be metabolically inert. After these reports no publications on the metabolism of PCP in animals appeared for the following 15 years.…”
Section: Metabolism Of Pentachlorophenol (Pcp) In Animals and Mansupporting
confidence: 89%
“…The bulk of the substrate was found in the urine, only small amounts were excreted with the faeces. After Betts et al (1955) confirmed the results of Deichmann et al as PCP in the urine of rabbits was not excreted in a conjugated form, PCP seemed to be metabolically inert. After these reports no publications on the metabolism of PCP in animals appeared for the following 15 years.…”
Section: Metabolism Of Pentachlorophenol (Pcp) In Animals and Mansupporting
confidence: 89%
“…Compounds of this type, which are metabolized to mercapturic acids in rabbits (Table V) include mono-, di-, and trihalogenonitrobenzenes Thorpe, 1955a,b, l956,1957a, 195th). This same enzyme probably conjugates glutathione with certain tetrahalogenonitrobenzenes that are metabolized to mercapturic acids (Bray, Hybs, James, and Thorpe, 1953;Betts, James, and Thorpe, 1955) by repIace- ment of nitro groups (Al-Kassab et al, 1963). The nitro group is also lost during mercapturic acid biosynthesis from certain trihalogenonitrobenzenes and from pentahalogenonitrobenzene (Betts, James, and Thorpe, 1955;Betts, Bray, James, and Thorpe, 1957), and it appears that the nitro group is lost where it is flanked by halogen atoms and there is another halogen atom in the ring, viz., k and 7.…”
Section: A Glutathione S-aryltransferasementioning
confidence: 99%
“…This same enzyme probably conjugates glutathione with certain tetrahalogenonitrobenzenes that are metabolized to mercapturic acids (Bray, Hybs, James, and Thorpe, 1953;Betts, James, and Thorpe, 1955) by repIace- ment of nitro groups (Al-Kassab et al, 1963). The nitro group is also lost during mercapturic acid biosynthesis from certain trihalogenonitrobenzenes and from pentahalogenonitrobenzene (Betts, James, and Thorpe, 1955;Betts, Bray, James, and Thorpe, 1957), and it appears that the nitro group is lost where it is flanked by halogen atoms and there is another halogen atom in the ring, viz., k and 7. With 1,3-dichloro-2-nitrobenzene (8), however, although the nitro group has two neighboring halogen atoms, an additional halogen atom is not present in the ring and no mercapturic acid is formed (Bray, James, and Thorpe, 1957b).…”
Section: A Glutathione S-aryltransferasementioning
confidence: 99%
See 1 more Smart Citation
“…In a number of other studies where sulfates, glucuronide ethers, and glycine conjugates have been formed as drug metabolites, it has been found that the rate of their elimination was greater than the rate of their formation (11)(12)(13)(14). Although this assumption must be employed cautiously, it appears to have validity in this particular study.…”
Section: 008)mentioning
confidence: 85%